2020
DOI: 10.3171/2019.7.spine19437
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of cervical sagittal vertical axis, cervical lordosis, and T1 slope on pain and disability outcomes after anterior cervical discectomy and fusion in patients without deformity

Abstract: OBJECTIVEUnderstanding what influences pain and disability following anterior cervical discectomy and fusion (ACDF) in patients with degenerative cervical spine disease is critical. This study examines the timing of clinical improvement and identifies factors (including spinal alignment) associated with worse outcomes.METHODSConsecutive adult patients were enrolled in a prospective outcomes database from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 37 publications
0
26
2
Order By: Relevance
“…[17][18][19] And the result of some studies indicated the Cobb angle, T1 slope and some other parameters are closely related to clinical outcomes. [20][21][22] To the best of our knowledge, few reports have described the effect of the difference between postoperative and preoperative sagittal balance on postoperative dysphagia after ACDF with Zero-P. Consequently, one objective of this retrospective analysis was to summarize and identify the effect of the cervical sagittal balance and other possible related factors on dysphagia. And provides for future spinal surgeries with evidence on how to reduce the incidence of dysphagia after ACDF with Zero-P.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] And the result of some studies indicated the Cobb angle, T1 slope and some other parameters are closely related to clinical outcomes. [20][21][22] To the best of our knowledge, few reports have described the effect of the difference between postoperative and preoperative sagittal balance on postoperative dysphagia after ACDF with Zero-P. Consequently, one objective of this retrospective analysis was to summarize and identify the effect of the cervical sagittal balance and other possible related factors on dysphagia. And provides for future spinal surgeries with evidence on how to reduce the incidence of dysphagia after ACDF with Zero-P.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al [ 61 ] (2016) reported no significant difference of HRQoL or number of fusion levels in patients had solid anterior cervical fusion without correlation with SVA or CL. Bao et al [ 62 ] (2017) and Lau et al [ 63 ] (2020) have also failed to identify significant association between CL and HRQoL outcomes in their cervical fusion cohort. This implies there could be a range of alignment providing forgiveness without affecting the HRQoL.…”
Section: “Why” Important?mentioning
confidence: 99%
“…N ´u ˜nez-Pereira et al 14 used C7 slope as an index of global sagittal balance in the cervical region and showed that there is no difference between C7 slope changes and function of patients after ACDF. Also, in a recent study, Lau et al 15 reported on a series of patients who underwent from single-level to 3-level ACDF and plate fixation. They found that cervical lordosis, C2-C7 SVA, and T1 slope were not significantly associated with functional outcomes, specifically NDI and VAS scores of the patients.…”
Section: Discussionmentioning
confidence: 99%